From Truman to Reagan: The Evolution of U.S. Nuclear Policy in the Cold War Context - Antidze, Maia (European Scientific Journal, ESJ, 2025)
This study explores the evolution of United States nuclear policy from 1945 to 1988, focusing on key presidential administrations from Harry Truman to Ronald Reagan. It investigates how nuclear strategy was adapted in response to geopolitical challenges, technological developments, and shifting diplomatic relations during the Cold War. Drawing on a qualitative analysis of multiple primary sources - such as presidential speeches, government archives, and contemporary media - as well as a critical review of significant secondary literature, including works by key scholars and historians, this research contextualizes pivotal policy decisions and strategic debates. By comparing interpretations from varying authors and incorporating both American and Soviet perspectives, the study critically examines tensions between deterrence and disarmament that shaped treaty negotiations and grand strategy. This nuanced approach highlights the interplay between nuclear policy and broader international security dynamics, offering insights into its role in concluding the Cold War.